Anemia: Increasing prevalence in general population: why? - Chandran, Rabindran; Gedam, D Sharad (International Journal of Medical Research and Review, 2015)
In India, various surveys showed that over 70 % of preschool children, pregnant women and adolescent girls were anaemic.